Amifostine reduces gastro-intestinal toxicity after autologous transplantation for multiple myeloma. Issue 8 (3rd August 2018) - Malek, Ehsan; Gupta, Vinita; Creger, Richard; Caimi, Paolo; Vatsayan, Anant; Covut, Fahrettin; Bashir, Qaiser; Champlin, Richard; Delgado, Ruby; Rondon, Gabriela; Cooper, Brenda; de Lima, Marcos; et al.
Abstract: High-dose melphalan (HDM) followed by autologous hematopoietic cell transplantation (auto-HCT) remains the standard-of-care therapy for multiple myeloma (MM) even with the availability of proteasome inhibitors and immunomodulatory drugs. Gastrointestinal (GI) toxicity is the main cause of morbidity after HDM. Amifostine, a cytoprotective agent, may reduce HDM-associated GI toxicity. We conducted a case control study comparing HDM + auto-HCT with or without amifostine for MM patients. One hundred and seven patients treated at University Hospitals Cleveland Medical Center who received pre-transplant amifostine were compared to 114 patients treated at MD Anderson Cancer Center without use of this agent. Amifostine 740 mg/m 2 was administered as a bolus infusion at 24 h and 15 min before HDM. Patients' characteristics were similar in both the groups. Amifostine therapy was well tolerated without any significant adverse effects. Grade II or greater oral mucositis (27.1% vs 47.4%; p  = .002), nausea (31.8% vs. 86.0%; p  = .0001), vomiting (18.7% vs. 52.6%; p  = .0001) and diarrhea (56.1% vs. 72.7%; p  = .006) occurred less frequently in the amifostine-treated group. There was no discernable effect of amifostine on engraftment, progression-free or overall survival. Our results indicate that amifostine decreases GI toxicity while preserving anti-myeloma efficacy of HDM and auto-HCT.